An investigation of water level fluctuations in Polish lakes in various phases of the winter North Atlantic Oscillation - Wrzesiński, Dariusz; Ptak, Mariusz (Geology, Geophysics and Environment, 2018)
The North Atlantic Oscillation is a macroscale type of circulation determining climate and hydrological conditions in Europe. The paper presents water level fluctuations in 19 Polish lakes in various phases of NAO of the winter season in the years 1976-2010. Correlations of the winter NAO index with monthly, seasonal, maximum, and minimum water stages, and annual water level amplitudes in lakes were calculated. Approximately 20% of the performed tests showed statistical significance. Lakes were recorded where the correlations were significant in a major part of the year, as well as lakes showing no significant correlations in any month. Deviations of mean water stages in the positive and negative phase of NAO from mean water stages were calculated for each of the lakes. This permitted classifying the lakes into two groups by Ward’s method based on deviations of water stages in the positive and negative phase of NAODJFMfrom average values. This resulted in the designation of 4 and 5 typological classes of lakes, respectively. Deviations of water stages in lakes in various phases of NAODJFMfrom mean values were determined to even exceed 20 cm. The study results can find practical applications in reference to water retention. In view of the observed environmental changes, it is possible that the hydrotechnical infrastructure on lakes will have to be developed in the future. Such a situation will permit the precise control of water level fluctuations for the purpose of the optimal adaptation of lakes for economic purposes.